THE INFLUENCE OF PROBLEM BASED LEARNING AND DISCOVERY LEARNING ASSISTED WITH ANIMATED VIDEO MEDIA ON STUDENTS' SCIENTIFIC LITERACY CAPABILITY ON CHEMICAL EQUILIBRIUM MATERIALS: PENGARUH PROBLEM BASED LEARNING DAN DISCOVERY LEARNING BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP KEMAMPUAN LITERASI SAINS SISWA PADA MATERI KESETIMBANGAN KIMIA - Sinuraya, Elsa; Susanti, Nora; Rismawati, Eni (UIN Mataram, 2024)
The aim of this research is to determine whether there is an increase and difference in the scientific literacy abilities of students who are taught using the Problem-Based Learning model and the Discovery Learning model assisted by animated video media on chemical equilibrium material. The population of this study was all students in class XI Science. The sampling technique was carried out using purposive sampling, resulting in class XI IPA 5, totaling 34 students, as experimental class I and XI IPA 6, totaling 36 students, as experimental class II. The results of students' scientific literacy abilities taught using the Problem-Based Learning model have increased with an average value from 47.05 to 82.94, as well as the results of students' scientific literacy abilities taught using the Discovery Learning model, namely with an average value of 44. 17 to 79.94. Through hypothesis testing using the Independent Sample T-Test with the prerequisites of normality and homogeneity, a Sig (2-tailed) value of 0.024 was obtained. So the value 0.024 < 0.05, so Ha is accepted. The results of this research show that there are differences in the scientific literacy abilities of students taught using the Problem-Based Learning model and the Discovery Learning model assisted by animated video media on chemical equilibrium material.